Recombinant human luteinizing hormone increases endometrial thickness in women undergoing assisted fertility treatments: a systematic review and meta-analysis - Mao, Routong; Hou, Xiaohong; Feng, Xiao; Wang, Ruina; Fei, Xiaofan; Zhao, Junzhao; Chen, Hui; Cheng, Jing (Frontiers in Pharmacology, 2024)
Introduction The optimal dosage of recombinant human luteinizing hormone (r-hLH) and its impact on endometrial thickness (EMT) when administered alongside recombinant human follicle-stimulating hormone (r-hFSH) during controlled ovarian stimulation (COS) for in vitro fertilization/intracytoplasmic sperm injection and embryo transfer are uncertain, which formed the aims of this systematic review and meta-analysis. Method A search was performed in PubMed, Cochrane Library, Web of Science, EMBASE, CNKI, and Wanfang from its inception to 10 July 2023. Twenty-seven Randomized controlled trials comparing r-hFSH/r-hLH co-treatment with r-hFSH alone during in vitro fertilization/intracytoplasmic sperm injection and embryo transfer (IVF/ICSI-ET) were included. Pooled odds ratios (OR) for dichotomous data and mean differences (MD) for continuous data, with their respective 95% confidence intervals (CI), were generated. Meta-analysis employed fixed-effect or random-effect models based on heterogeneity, using Q-test and I2-index calculations. The main outcomes included EMT on trigger day, clinical pregnancy rate (CPR) and live birth rate (LBR). Results r-hFSH/r-hLH significantly increased EMT on trigger day (MD = 0.27; 95% CI, 0.11–0.42; I2 = 13%), but reduced oocyte number (MD = −0.60; 95% CI, −1.07 to −0.14; I2 = 72%) and high-quality embryos (MD = −0.76; 95% CI, −1.41 to −0.10; I2 = 94%) than r-hFSH alone, more pronounced with the gonadotrophin-releasing hormone agonist long protocol. A subgroup analysis showed r-hLH at 75 IU/day increased CPR (OR = 1.23; 95% CI, 1.02–1.49; I2 = 16%) and EMT on trigger day (MD = 0.40; 95% CI, 0.19–0.61; I2 = 0%). Participants ≥35 years of age exhibited decreased retrieved oocytes (MD = −1.26; 95% CI, −1.78 to −0.74; I2 = 29%), but an increase in EMT on trigger day (MD = 0.26; 95% CI, 0.11–0.42; I2 = 29%). Conclusion r-hFSH/r-hLH during COS significantly improved EMT compared to r-hFSH alone. An r-hLH dose of 75 IU/day may be considered for optimal pregnancy outcomes, which still require further clinical studies to support this dosing regime. Systematic Review Registration [www.crd.york.ac.uk/PROSPERO], identifier [CRD42023454584].